2021
DOI: 10.1039/d1gc00775k
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of enzyme@metal–organic material (MOM) biocomposites for enzyme biocatalysis

Abstract: Metal-Organic Frameworks/Materials (MOFs/MOMs) are advanced enzyme immobilization platforms that improve biocatalysis, materials science, and protein biophysics. A unique way to immobilize enzymes is co-crystallization/co-precipitation, which removes the limitation on enzyme/substrate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In order to preserve catalytic activity, macromolecules have been added in some of these one-pot systems: mixing polyvinylpyrrolidone (PVP) with Cyt C prior to the immobilization process in ZIF-8 [32] to form a double layer to protect its activity and stability. A lignin derivative (DDVA) has also been used to co-precipitate enzymes with Ca 2+ or Zn 2+ to yield enzyme@MOM composites [41]. Additionally, Fe 3 O 4 has successfully been added to provide particles with magnetic properties such as in the one-pot synthesis involving 2-methylimidazole and zinc acetate with lipase from Candida rugosa in the MOF CRL/MNP@ZIF-8 [42].…”
Section: The Origins and Rising Dominance Of The Enzyme-supporting Mofmentioning
confidence: 99%
“…In order to preserve catalytic activity, macromolecules have been added in some of these one-pot systems: mixing polyvinylpyrrolidone (PVP) with Cyt C prior to the immobilization process in ZIF-8 [32] to form a double layer to protect its activity and stability. A lignin derivative (DDVA) has also been used to co-precipitate enzymes with Ca 2+ or Zn 2+ to yield enzyme@MOM composites [41]. Additionally, Fe 3 O 4 has successfully been added to provide particles with magnetic properties such as in the one-pot synthesis involving 2-methylimidazole and zinc acetate with lipase from Candida rugosa in the MOF CRL/MNP@ZIF-8 [42].…”
Section: The Origins and Rising Dominance Of The Enzyme-supporting Mofmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are advanced platforms for enzyme immobilization and have provided advancement in biocatalysis, biomedicine, and fundamental biophysics research. Thus far, major efforts in enzyme@MOF research have been focused on optimizing the metal, ligand, aperture, and/or pores of MOFs to enhance enzyme protection (against the reaction medium), reusability (as a result of the ease of separation), and substrate selectivity and/or diffusivity. , While preformed, highly stable, and crystalline MOFs are mostly applied to host relatively small enzymes with small substrates, “one-pot” synthesis via co-crystallization of large enzymes and/or enzyme clusters with metals and ligands in the aqueous phase (also known as biomimetic mineralization) has been shown to be effective in removing the size limitation of enzymes. , Recently, researchers including our team have shown the possibility of using co-precipitation to remove the size limitation of the substrate, so that the entrapped enzymes are partially exposed to the reaction medium and partially buried under the MOF crystal surfaces, as demonstrated on zeolitic imidazolate frameworks (ZIFs) and recent Ca-based metal–organic materials (MOMs, an analogue of MOFs but with a one- or two-dimensional structure); , the exposed enzyme regions were also revealed using our developed biophysical tools. , Importantly, our enzyme@Ca-MOM composites can be formed in the enzyme-friendly, aqueous phase under ambient conditions, minimizing the enzyme loss during co-precipitation . The Ca-MOMs are also stable under both weakly acidic and basic conditions, allowing for biocatalysis under the optimal pH of the immobilized enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent discovery, we found that an enzyme can be partially exposed above the surface of metal–organic frameworks/materials (MOFs/MOMs) upon co-crystallization while being partially buried (and thus, protected) in the scaffolds; here, MOMs are usually referred to as 1D or 2D structures, while MOFs are 3D frameworks according to a strict definition . This strategy can offer enhanced enzyme protection to a satisfying extent so that a reasonable number of reuse cycles can be achieved.…”
Section: Introductionmentioning
confidence: 99%